Sikkim-the Country and its Forests - Choudhury, K. C. Roy (Indian Forester, 1951)
Sikkim is an inconspicuous place in the map, and is the smallest of our neighbours; Though a very small state in area, it is perhaps one of the richest places in the Eastern Himalayas in both vegetable and animal life. Rhododendrons, Primulas, Potentilas and orchids are the real glory of Sikkim. The A vi-fauna and butterfly have got a long range in numbers. The country is picturesque and there are any number of snow-fields and glaciers and lakes to trek about. It is a veritable naturalist's paradise. Among its flora are genera that are only to be found in America, Europe, Japan, Siberia, and even in the Arctic. It is quite interesting from the anthropological standpoint too.